Representation Of Symbolic Violence In Infidelity (Studies On Operas The Inner Voice Of Wife Episode “Making Friends Does Not Mean Sharing A Husband”) - Aisyah, Nur; Endang, Anis; Asnawati, Asnawati (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
In Most of the opera theme in Indonesia ranges from about love between men and women or retaliation spawned violent scenes. Var Through the opera, The Voice of the Wife's Heart, the Friendly Episode Does Not Mean Sharing Husband is available, the media can display a picture of symbolic violence perpetrated by women against their friends. Ious forms of symbolic violence that are shown in operas. This study aims to look at representations of symbolic violence which refers to Law no. 23 of 2004 concerning the Elimination of Domestic Violence. The methodology used in this research is descriptive qualitative with the method of semiotic analysis by Roland Barthes. The data obtained for this analysis is obtained through selecting a scene in which there is an element of symbolic violence. Then, after selecting the data, they are grouped according to the form of symbolic violence they get. While the theory used is Roland Barthes' semiotic theory which consists of denotation, connotation and myth. The results showed that symbolic violence against women was shown various kinds of symbolic violence such as threats and belittling, as well as signs of ideology in operas the conscience of the wife in the friendly episode does not mean sharing the husband either symbolically or visually. And the ideology contained in the opera The Voice of the Heart for a Friendly Wife Doesn't Mean Sharing Husband is a patriarchal ideology.